Efektivitas Model Cooperative Integrated Reading and Composition dalam Pembelajaran Mengubah Teks Wawancara Menjadi Karangan Narasi - Mattoliang, Ridwan Andi; Amin, Muliaty (Faculty of Tarbiyah and Teacher Training, 2023)
Writing is one of the language skills that students must have. This research examines the effectiveness of using the Cooperative Integrated Reading and Composition model in learning to convert interview text into narrative for class VII students at SMP Negeri 4 Sengkang. The type of research used is experimental research. This research uses a quasi-experimental design. The population in this study was all class VII students, totaling 85 students. The research sample was class VII B as the experimental class, totaling 21 students and class VII A as the control class, totaling 21 students. The collected data was then analyzed using descriptive and inferential statistical analysis. The research results show that the Cooperative Integrated Reading and Composition model is effectively applied in learning to convert interview text into narrative for class VII students at SMP Negeri 4 Sengkang. Implementation of this model can provide the basis for more interactive and supportive cooperative learning, with a focus on developing language skills